2015
DOI: 10.1039/c4tc02136c
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Dion–Jacobson ABiNb2O7(A = Rb, Cs) compounds

Abstract: Ferroelectricity and piezoelectricity in CsBiNb2O7 are demonstrated for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 20 publications
1
42
2
Order By: Relevance
“…First-principles density functional theory (DFT) calculations show that the symmetry can be broken and ferroelectric properties can be achieved with a combination of layered cation ordering and OORs. [ 15,16 ] Recently, an n = 1 Ruddlesden-Popper family (Na R TiO 4 ; R = rare earth) was experimentally determined to be piezoelectric, yet nonpolar. [ 9 ] To date, there is only a small group of well-characterized layered oxide ferroics, which include some Aurivillius phases (e.g., SrBi 2 Ta 2 O 7 [ 10 ] and its derivatives, [ 11 ] and CaBi 2 Nb 2 O 9 [ 12 ] ), a Ruddlesden-Popper phase Sr n +1 Ti n O 3 n +1 ( n = 1-6), [ 13 ] and the Dion-Jacobson (DJ) phases RbBiNb 2 O 7 , [ 14 ] CsNdNb 2 O 7 , [ 15 ] and CsBiNb 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%
“…First-principles density functional theory (DFT) calculations show that the symmetry can be broken and ferroelectric properties can be achieved with a combination of layered cation ordering and OORs. [ 15,16 ] Recently, an n = 1 Ruddlesden-Popper family (Na R TiO 4 ; R = rare earth) was experimentally determined to be piezoelectric, yet nonpolar. [ 9 ] To date, there is only a small group of well-characterized layered oxide ferroics, which include some Aurivillius phases (e.g., SrBi 2 Ta 2 O 7 [ 10 ] and its derivatives, [ 11 ] and CaBi 2 Nb 2 O 9 [ 12 ] ), a Ruddlesden-Popper phase Sr n +1 Ti n O 3 n +1 ( n = 1-6), [ 13 ] and the Dion-Jacobson (DJ) phases RbBiNb 2 O 7 , [ 14 ] CsNdNb 2 O 7 , [ 15 ] and CsBiNb 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Their unique structure leads to many interesting properties, making them of interest for many applications, including for solar cells, 1,2 water splitting 3,4 and ferroelectrics. [5][6][7] It is known that DJ phase materials can be exfoliated into nanosheets due to the large interlayer spacing and weak bonding of the A 0 layers. M. Hojamberdiev et al 3 exfoliated the centrosymmetric, non-polar, three-layer compound CsBa 2 Ta 3 -O 10 by a sequence of steps involving nitridation-protonationintercalation to produce nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, exciting new results have emerged that demonstrate ferroelectricity in the non-centrosymmetric, polar, twolayer DJ phase ABiNb 2 O 7 (A ¼ Rb, Cs). 6,7 Like some simple perovskites (e.g. BaTiO 3 ), their spontaneous polarization originates from displacement of the A-site cations and tilting of the octahedra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our follow-up experimental studies [16] on CsBiNb 2 O 7 suggested that ferroelectricity was hindered by moisture uptake, leading to proton conductivity and leakage. Nevertheless, a more recent work by Chen et al [17] did provide experimental evidence for ferroelectricity in this compound. Goff et al [16], attempted to determine any high temperature phase transitions in CsBiNb 2 O 7 using powder neutron diffraction: no evidence for phase transitions was identified up to 900 • C, above which sample deterioration precluded further study.…”
Section: Introductionmentioning
confidence: 99%